A Bruise Without a Name: Investigating College Student Perceptions of Intimate Partner Violence Terminology - Nordin, Karin (Journal of interpersonal violence, 2021)
When it comes to intimate partner violence, words matter. The abuse terminology used in efforts to target collegiate victims of intimate partner violence (IPV) can impact the effectiveness of prevention messages. The purpose of this study is twofold: first, to identify the relationship between abuse labels (such as domestic violence, dating violence, and IPV), and bystander intervention recommendations. Second, this study aims to understand how situational factors (perpetrator gender, couple marital status, provocation) impact the perceived appropriateness of those terms. Perceptions of severity, victim/perpetrator blame, and bystander intervention recommendations were also measured. In all, 498 college students from a large southern public university participated in a 2 × 2 × 2 experiment where they read a vignette depicting IPV. Participants were then asked a serious of questions about the appropriateness of the abuse terminology, what actions they would recommend for a bystander, the severity of the incident, and the degree to which they blamed victim and perpetrator. Results indicated the bystander intervention actions that are perceived as appropriate are related to what the most appropriate label is for the situation. Contextual factors surrounding the IPV situation, such as perpetrator gender, couple marital status, and provocation, influenced bystander recommendations and what labels were considered appropriate. The results of the study indicate the need to expand collegiate definition of what “counts” as IPV and point to ways in which IPV context can be a barrier to bystander intervention. Implications of the study argue that efforts to increase bystander intervention must include training on how to identify IPV situations with a broad variety of contexts. Limitations of the study and implications for theory and practice are discussed.